Synthetic Lipoteichoic Acid Glycans Are Potential Vaccine Candidates to Protect from Clostridium difficile Infections. Issue 8 (18th August 2016) - Broecker, Felix; Martin, Christopher E.; Wegner, Erik; Mattner, Jochen; Baek, Ju Yuel; Pereira, Claney L.; Anish, Chakkumkal; Seeberger, Peter H.
Summary: Infections with Clostridium difficile increasingly cause morbidity and mortality worldwide. Bacterial surface glycans including lipoteichoic acid (LTA) were identified as auspicious vaccine antigens to prevent colonization. Here, we report on the potential of synthetic LTA glycans as vaccine candidates. We identified LTA-specific antibodies in the blood of C. difficile patients. Therefore, we evaluated the immunogenicity of a semi-synthetic LTA-CRM197 glycoconjugate. The conjugate elicited LTA-specific antibodies in mice that recognized natural LTA epitopes on the surface of C. difficile bacteria and inhibited intestinal colonization of C. difficile in mice in vivo. Our findings underscore the promise of synthetic LTA glycans as C. difficile vaccine candidates. Graphical Abstract: Highlights: Lipoteichoic acid (LTA) glycan antigens of Clostridium difficile were synthesized The synthetic LTA glycans are recognized by antibodies of C. difficile patients Formulated as a glycoprotein, LTA glycans elicit strong IgG responses in mice Immunization with the LTA glycoprotein protects mice from challenge with C. difficile Abstract : Broecker et al. show that synthetic lipoteichoic acid (LTA) glycan antigens derived from Clostridium difficile resemble epitopes of the natural polysaccharide. The synthetic LTA antigens are able to induce antibodies in mice that protect from infection with C. difficile .